Clinical and laboratory signs of haemophagocytic lymphohistiocytosis associated with pandemic influenza A (H1N1) infection in patients needing extracorporeal membrane oxygenation: A retrospective observational study. Issue 7 (July 2021) - von Bahr Greenwood, Tatiana; Holzgraefe, Bernhard; Chiang, Samuel C.C.; Wang, Yini; Tesi, Bianca; Bryceson, Yenan T.; Henter, Jan-Inge
Abstract : BACKGROUND: Severe pandemic influenza has been associated with the hyperinflammatory condition secondary haemophagocytic lymphohistiocytosis (HLH). OBJECTIVES: To determine the frequency, degree, character and possible cause of influenza-associated HLH in critically ill patients with severe acute respiratory distress syndrome due to influenza A (H1N1) infection requiring extracorporeal membrane oxygenation (ECMO) support at our hospital. DESIGN: A retrospective observational study. PATIENTS AND SETTING: Medical data were retrieved retrospectively from 11 consenting patients of thirteen adults infected with pandemic influenza A (H1N1) 2009 requiring ECMO between July 2009 and January 2010 at the ECMO Centre of Karolinska University Hospital, Stockholm, Sweden. All patients were evaluated for HLH using HLH-2004 criteria and HScore. RESULTS: Eleven patients (median age 31 years) were included in the study and all survived. All patients showed signs of multiple organ dysfunction and pronounced inflammation, more severe in the four patients with HLH who had significantly higher peak serum concentrations of ferritin ( P  = 0.024), alkaline phosphatase ( P  = 0.012) and gamma-glutamyl transferase ( P  = 0.024), lower concentration of albumin ( P  = 0.0086) and more frequently hepatomegaly ( P  = 0.048). Abnormal lymphocyte cytotoxicity (lytic units <10) and a low proportion of natural killer (NK) cells were observed in three of four patients with HLH. Notably, we found a significant inverse correlation between serum ferritin concentration and NK cell and cytotoxic T lymphocyte percentages ( r s  = −0.74, P  = 0.0013 and r s  = −0.79, P  = 0.0025, respectively). One HLH patient received HLH-directed cytotoxic therapy, another intravenous immunoglobulin and the other two no specific HLH-directed therapy. CONCLUSION: Critically ill patients, including healthy young adults, with pandemic influenza may develop HLH and should be monitored for signs of hyperinflammation and increasing organ dysfunction, and evaluated promptly for HLH because HLH-directed therapy may then be beneficial. The association of low NK percentages with hyperferritinaemia may suggest a role for reduced NK cell numbers, possibly also cytotoxic T lymphocytes, and subsequently reduced lymphocyte cytotoxicity, in the pathogenesis of hyperinflammation and secondary HLH.